Detection of Cosmological 21 cm Emission with the Canadian Hydrogen Intensity Mapping Experiment - The CHIME Collaboration; Mandana Amiri; Kevin Bandura; Tianyue Chen; Meiling Deng; Matt Dobbs; Mateus Fandino; Simon Foreman; Mark Halpern; Alex S. Hill; Gary Hinshaw; Carolin Höfer; et al. (The Astrophysical Journal, 2023)
We present a detection of 21 cm emission from large-scale structure (LSS) between redshift 0.78 and 1.43 made with the Canadian Hydrogen Intensity Mapping Experiment. Radio observations acquired over 102 nights are used to construct maps that are foreground filtered and stacked on the angular and spectral locations of luminous red galaxies (LRGs), emission-line galaxies (ELGs), and quasars (QSOs) from the eBOSS clustering catalogs. We find decisive evidence for a detection when stacking on all three tracers of LSS, with the logarithm of the Bayes factor equal to 18.9 (LRG), 10.8 (ELG), and 56.3 (QSO). An alternative frequentist interpretation, based on the likelihood ratio test, yields a detection significance of 7.1 σ (LRG), 5.7 σ (ELG), and 11.1 σ (QSO). These are the first 21 cm intensity mapping measurements made with an interferometer. We constrain the effective clustering amplitude of neutral hydrogen (H i ), defined as ${{ \mathcal A }}_{{\rm{H}}\,{\rm\small{I}}}\equiv {10}^{3}\,{{\rm{Ω }}}_{{\rm{H}}\,{\rm\small{I}}}\left({b}_{{\rm{H}}\,{\rm\small{I}}}+\langle \,f{μ }^{2}\rangle \right)$ , where Ω _H _i is the cosmic abundance of H i , b _H _i is the linear bias of H i , and 〈 f μ ^2 〉 = 0.552 encodes the effect of redshift-space distortions at linear order. We find ${{ \mathcal A }}_{{\rm{H}}\,{\rm\small{I}}}={1.51}_{-0.97}^{+3.60}$ for LRGs ( z = 0.84), ${{ \mathcal A }}_{{\rm{H}}\,{\rm\small{I}}}={6.76}_{-3.79}^{+9.04}$ for ELGs ( z = 0.96), and ${{ \mathcal A }}_{{\rm{H}}\,{\rm\small{I}}}={1.68}_{-0.67}^{+1.10}$ for QSOs ( z = 1.20), with constraints limited by modeling uncertainties at nonlinear scales. We are also sensitive to bias in the spectroscopic redshifts of each tracer, and we find a nonzero bias Δ v = − 66 ± 20 km s ^−1 for the QSOs. We split the QSO catalog into three redshift bins and have a decisive detection in each, with the upper bin at z = 1.30 producing the highest-redshift 21 cm intensity mapping measurement thus far.